(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the work done to study the scientific heritage of Asomiddin Urinbaev, a well-known Uzbek historian, Honored Scientist of Uzbekistan, Doctor of Historical Sciences, winner of the State ‘rize named after Abu Rayhon Beruni. Although A. Urinbaev is well-known as a Temurologist, it was revealed that he was also active in the study of the history of Kokand.